2021
DOI: 10.1001/jamanetworkopen.2021.22320
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Telehealth Medication Abortions in the US During the COVID-19 Pandemic

Abstract: This cohort study examines the safety and efficacy of fully remote, asynchronous medication abortion care during the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 7 publications
2
80
0
2
Order By: Relevance
“…Among the 425 TelAbortion Study participants in this analysis, outcomes of 346 were reported in a previously published paper. Additionally, we included outcomes of 117 patients and 111 patients reported in previous articles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 425 TelAbortion Study participants in this analysis, outcomes of 346 were reported in a previously published paper. Additionally, we included outcomes of 117 patients and 111 patients reported in previous articles.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies, primarily in the UK and Canada, have concluded that history-based screening for medication abortion is safe and effective. The largest, which included 18 435 medication abortions in the UK provided without screening ultrasonography, reported that 99% were complete without intervention, and serious adverse events occurred in 0.02%. An analysis of data from 425 participants in the TelAbortion study, a prospective multicenter study of medication abortions provided by telemedicine and mail conducted in the US, also found high effectiveness and safety in the subset screened by history alone, although these patients had lower effectiveness rates (94%) than those who had had pretreatment tests (98%).…”
Section: Introductionmentioning
confidence: 99%
“…We look forward to completing recruitment for the study in the coming year, which will provide more precise estimates of the effectiveness, acceptability, and feasibility of medication abortion with mail-order pharmacy dispensing of mifepristone. However, these interim results, together with studies of other care models that include mailing pills for medication abortion [23][24][25][26] and pharmacist dispensing at brick-and-mortar pharmacies [3], support the removal of the FDA's in-person dispensing requirement for mifepristone.…”
Section: Discussionmentioning
confidence: 96%
“…In the United States, models such as ExPAND Mifepristone demonstrate that learning collaborations that provide evidence-based knowledge on the clinical use of mifepristone and expertise on best practices to navigate the administrative logistics are important aspects of reducing logistical and psychological barriers to abortion provision in primary settings [ 30 ]. In addition, recent models of online provision of medication abortion by family physicians provide encouraging direction for expanding care [ 31 , 32 ]. These broad efforts will likely be necessary, alongside the full elimination of the REMS, to reduce stigma and optimize provision of medication abortion in primary care settings.…”
Section: Discussionmentioning
confidence: 99%